1998
DOI: 10.1021/es9709076
|View full text |Cite
|
Sign up to set email alerts
|

DMS Formation by Dimethylsulfoniopropionate Route in Freshwater

Abstract: Dimethyl sulfide, the most important form of sulfur gas, is formed by bacterial degradation of dimethylsulfoniopropionate (DMSP) in the Lake of Galilee. DMSP is believed to be a methionine metabolite produced by marine algae and higher plants as part of their osmoregulatory systems. Until now, this process was found exclusively in saline water and therefore was regarded as insignificant for the formation of DMS in freshwaters. It is hereby demonstrated that the process can be dominant in freshwater systems as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 29 publications
7
44
0
Order By: Relevance
“…NH 4 + -N increased tenfold to twentyfold when DO was depleted quickly to zero. These increases agree with some previous studies, which indicated that cyanobacteria cell lysis resulted in a large release of nutrients (Ginzburg et al, 1998a(Ginzburg et al, , 1998bYe et al, 2010). Nutrients released during the decomposition of cyanobacterial blooms represent a potential source of internal nutrient loading to lakes.…”
Section: Discussionsupporting
confidence: 92%
“…NH 4 + -N increased tenfold to twentyfold when DO was depleted quickly to zero. These increases agree with some previous studies, which indicated that cyanobacteria cell lysis resulted in a large release of nutrients (Ginzburg et al, 1998a(Ginzburg et al, , 1998bYe et al, 2010). Nutrients released during the decomposition of cyanobacterial blooms represent a potential source of internal nutrient loading to lakes.…”
Section: Discussionsupporting
confidence: 92%
“…Although a freshwater dinoflagellate (Peridinium gatunense) was found to be able to store DMSP (Ginzburg et al 1998), to our knowledge, the presence of DMSP in freshwater algae or the water column has not yet been reported in other freshwater lakes. Therefore, DMSP is unlikely to be the precursor of the MPA detected in Linsley Pond.…”
Section: Discussionmentioning
confidence: 67%
“…These variations can be explained as follows. For the VOSCs, stored dimethylsulfoniopropionate (DMSP) in the algal cells could first be released into the ambient water column during the massive and rapid anaerobic algal decay (Ginzburg et al, 1998). Then, DMSP could lead to a rapid increase in DMS production by other microbes and via physicochemical degradation (Li et al, 2011).…”
Section: Dynamics Of Taste and Odor Compounds In Black Bloommentioning
confidence: 99%